Collage Meets Design - Chamorro, Jorge (HOAKI, 2023)
This book presents a selection of contemporary graphic design studios, collage artists and artists from other disciplines in whose work design and collage intersect in the most diverse and witty ways. It features projects in which different languages and techniques mix, dialogue with each other, complement each other, sometimes dilute each other and question their respective limits. Through this showcase of design projects and art pieces, and through conversations with their authors, we learn about their unique approaches to the creative process, reflect on ways of understanding their work and investigate the special relationship that design and collage have today
9788417656898
Keywords: Hardcover; Softcover / Sachbücher/Kunst; Literatur/Sonstiges; Collage; Kunst; Papier; Schere; cut and paste; Ausschneiden und Einfügen; Zeichnung; Ausschnitt; Malerei; Kunsttechniken; Kleber; Arbeitsbuch; Aktivitätsbuch; Künstler; Kreativität; Design; Illustration; Grafikdesigner; Grafildesign; Cut-and-Paste; Mischtechnik